When federalism works - Peterson, Paul E.; Rabe, Barry George; Wong, Kenneth K. (Washington, D.C. : Brookings Institution, 1986)
In this study the authors explore the conventional wisdom on federal grants by examining the operations of nine important federal programs in education, health care, and housing.
Includes bibliographical references and index.
osa 22/01/19
Loans
Keywords: Federal government; Intergovernmental fiscal relations; Grants-in-aid; United States